2021
DOI: 10.36995/j.recyt.2021.36.004
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of aqueous extraction of phenolic compounds from processed yerba mate leaves

Abstract: In this study, the kinetics of aqueous extraction of phenolic compounds from the yerba mate leaves were analyzed. A temperature range between 40°C and 70°C and a ratio of 25 g of mate leaves in 200 mL of water were used. The extraction kinetic was studied adjustment of the kinetics models of first order, second order kinetic model and the second order diffusive model. The goodness of the fit was controlled by the magnitude of the coefficient of determination (R2), the percentage error (EP %) and the square roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The second-order model demonstrates a firm fit, aligning with the first-order R 2 values, indicating a reasonable model agreement. This finding is consistent with previous research that found the second-order kinetic model suitable for describing adsorption processes, as it provides essential information about the initial extraction process and the mechanism occurring in the final extraction stage 74 . Furthermore, the literature supports the use of second-order kinetics for modeling and predicting the behavior of adsorption systems under various operating conditions, emphasizing this model’s applicability in understanding and optimizing adsorption processes 75 .…”
Section: Resultssupporting
confidence: 92%
“…The second-order model demonstrates a firm fit, aligning with the first-order R 2 values, indicating a reasonable model agreement. This finding is consistent with previous research that found the second-order kinetic model suitable for describing adsorption processes, as it provides essential information about the initial extraction process and the mechanism occurring in the final extraction stage 74 . Furthermore, the literature supports the use of second-order kinetics for modeling and predicting the behavior of adsorption systems under various operating conditions, emphasizing this model’s applicability in understanding and optimizing adsorption processes 75 .…”
Section: Resultssupporting
confidence: 92%
“…The rapid increase in TPC levels in the initial stage of the US‐assisted extraction may be related to swelling and dilatation of the capillaries of the YM leaves (washout mechanism). Whereas, the second decelerated stage may be attributed to the diffusion of the polyphenol compounds until equilibrium was reached (López et al, 2021). For the control extraction assay (conventional procedure: 5 min; 100°C), the obtained TPC value was higher (6.44 ± .03 g GAE/L), compared to the proposed US‐assisted extraction.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, López et al (2021) characterized the kinetics of the aqueous extraction of phenolic compounds from YM leaves (25 g leaves: 200 mL water) in a conventional batch operation (40–70°C, .5–60 min). Likewise, they obtained a steep increase in the concentration of polyphenol compounds during the first few minutes of extraction, followed by a slower stage that approached the equilibrium polyphenol compounds concentration (~30 min).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations